Experimental Investigation of AdBlue Film Formation in a Generic SCR Test Bench and Numerical Analysis Using LES - Anna Schmidt; Matthias Bonarens; Ilia V. Roisman; Kaushal Nishad; Amsini Sadiki; Andreas Dreizler; Jeanette Hussong; Steven Wagner (Applied Sciences, 2021)
In this work, an experimental investigation of AdBlue film formation in a generic selective catalytic reduction (SCR) exhaust gas test bench is presented. AdBlue is injected into a generic SCR test bench resulting in liquid film formation on the lower wall of the channel. The thickness of this liquid film is measured using a film thickness sensor based on absorption spectroscopy. Simultaneously, the wall temperature at the measurement point is monitored, which allows for examining correlations between the evolution of the film thickness and the temperature of the wetted wall. The velocity of the airflow in the channel and the initial wall temperature are varied in the experiments. Correspondingly, the measurements are performed during different thermodynamic regimes, including liquid film deposition and boiling. Repeated measurements have also shown that the film thicknesses are reproducible with a standard deviation of 3.4 %. LES-based numerical simulations are compared to the experimental results of the film thickness during the early injection stage. Finally, a numerical analysis is performed to analyze the AdBlue droplet impingement and subsequent film-formation dynamics.